2017
DOI: 10.1016/j.juro.2017.01.080
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Arterial Blood Supply to the Penis and the Accessory Pudendal Artery: A Meta-Analysis and Review of Implications in Radical Prostatectomy

Abstract: A penile blood supply originating at least in part from an accessory pudendal artery represents more than a third of cases. Based on the anatomical findings when an accessory pudendal artery is present, we advocate attempted preservation of the vessel during radical prostatectomy to best maintain the penile arterial blood supply, especially in patients with type 3 or in older patients with type 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 25 publications
0
16
0
3
Order By: Relevance
“…The APA is defined as any artery located in the periprostatic region running parallel to the dorsal vascular complex and extending caudal toward the anterior perineum. A recent meta-analysis, [ 28 ] evaluating 23 studies, reported that the APA was present in 28.5% of patients. When present, unilateral accessory pudendal arteries were most common (pooled prevalence estimate 72.5%), or they were present on the right or the left side (pooled prevalence estimate 48.0 or 52.0%, respectively).…”
Section: Prostate Arterial Supply: Artery-sparing Surgery Myth or Reamentioning
confidence: 99%
“…The APA is defined as any artery located in the periprostatic region running parallel to the dorsal vascular complex and extending caudal toward the anterior perineum. A recent meta-analysis, [ 28 ] evaluating 23 studies, reported that the APA was present in 28.5% of patients. When present, unilateral accessory pudendal arteries were most common (pooled prevalence estimate 72.5%), or they were present on the right or the left side (pooled prevalence estimate 48.0 or 52.0%, respectively).…”
Section: Prostate Arterial Supply: Artery-sparing Surgery Myth or Reamentioning
confidence: 99%
“…The proportion of men with APAs varies according to the method used to detect them. Incidence has ranged from 4%–75% in radiological and pathological studies [ 6 , 13 - 18 ]. In a retrospective clinical study, Park, et al suggested a possible connection between APA preservation and postsurgical functional outcome [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, we can’t identify APAs intraoperatively. Since 60% of APAs are the apical type, it is often impossible to confirm APAs during surgery [ 18 ]. However, we believe that tracing of APAs by MRI and 3D modeling is likely to provide more accurate information about the incidence and anatomical associations of APAs.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, a meta-analysis by Henry and colleagues introduced two potential issues. 20 First, they recommend preservation of the APA in 5.4% of men with penile blood supplied solely by an APA-an observation based on a cadaveric study by Droupy and colleagues in 1996. 21 It is important to recognize that the presence or absence of internal pudendal arteries (IPA) cannot be determined because these arteries course outside of the levator ani.…”
Section: Discussionmentioning
confidence: 99%